2017
DOI: 10.1620/tjem.243.67
|View full text |Cite
|
Sign up to set email alerts
|

Medical Discrimination Affects the HIV/AIDS Epidemic Control: A Study of Self-Perceived Medical Discrimination on People Living with HIV or AIDS

Abstract: People living with HIV or AIDS (PLWHA) experienced severe medical discrimination which is seriously affecting their lives. However, few studies examined the epidemic characteristics of self-perceived medical discrimination from the discrimination objects such as PLWHA. Therefore, we aimed to investigate the epidemiological status and analyze the influential factors of the self-perceived medical discrimination on PLWHA in South China. The self-designed questionnaire was used to investigate the medical discrimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…They deemed such behaviors a form of discrimination. Likewise, it has been reported in studies conducted in different countries that the participant PLWH were subjected to discrimination in healthcare environments and thus refused to seek healthcare services [71][72][73][74]. There are also studies in Turkey that demonstrated the stigma and discrimination in healthcare settings at both institutional and individual levels against PLWH [34,38].…”
Section: Discussionmentioning
confidence: 99%
“…They deemed such behaviors a form of discrimination. Likewise, it has been reported in studies conducted in different countries that the participant PLWH were subjected to discrimination in healthcare environments and thus refused to seek healthcare services [71][72][73][74]. There are also studies in Turkey that demonstrated the stigma and discrimination in healthcare settings at both institutional and individual levels against PLWH [34,38].…”
Section: Discussionmentioning
confidence: 99%
“…The three types of HIV-related stigma include self-perceived stigma, internalized stigma, and experienced stigma, 10 which commonly occur in three areas: social and community area, medical and health work area, and self-perceived stigma or personal perception, 18 of which self-perceived stigma was found to more negatively impact overall well-being among PLWHIVs than external discrimination. 19 However, research on HIV-related stigma and discrimination has been mainly focused on health care providers' and public's perspective, whereas there is paucity of research on discrimination under PLWHIV's perspective, who are the discrimination objects.…”
Section: Introductionmentioning
confidence: 99%
“… 19 However, research on HIV-related stigma and discrimination has been mainly focused on health care providers' and public's perspective, whereas there is paucity of research on discrimination under PLWHIV's perspective, who are the discrimination objects. 18 …”
Section: Introductionmentioning
confidence: 99%
“…They deemed such behaviors as a form of discrimination. Likewise, it was reported in a study conducted in South China that almost half of the PLWH participating in the study were subjected to discrimination in healthcare environments and thus refused to benefit from healthcare services (66). In a study carried out in Kazakhstan, it was found that PLWH experience denial of services by healthcare professionals and tend to avoid healthcare professionals due to such perceived negative attitudes (67).…”
Section: Discussionmentioning
confidence: 90%